An algorithm for arranging response surface designs in small blocks - Trinca, L. A.; Gilmour, S. G. (Elsevier B.V., 2000)
We consider the problem of blocking response surface designs when the block sizes are prespecified to control variation efficiently and the treatment set is chosen independently of the block structure. We show how the loss of information due to blocking is related to scores defined by Mead and present an interchange algorithm based on scores to improve a given blocked design. Examples illustrating the performance of the algorithm are given and some comparisons with other designs are made. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: blocking; scores; interchange algorithm; second-order model; central composite design; Box-Behnken design; weighted mean efficiency factor